The relationship of language anxiety with noticing and oral production of L2 forms: A study of beginning learners of Arabic. (February 2019) - Nassif, Lama
Abstract: This study investigated the relationship between foreign language anxiety (FLA) and the noticing and integration of second language (L2) forms. 80 beginning-level learners of Arabic were assigned to two treatment conditions, Output and Input, to explore whether FLA differentially associates with noticing under different task conditions. The Output group participants provided an oral description of a picture story, listened to, read, and underlined an Arabic speaker's description, and re-described pictures. The Input group participants answered pre-text exposure questions, listened to, read, and underlined a description, and answered post-text exposure questions. An immediate posttest, a delayed posttest, and interviews were administered afterwards. Interestingly, FLA positively associated with general form noticing and integration but did not predict learner noticing and integration of the future tense. No differential anxiety influences on learner noticing were detected across the Input and Output conditions.